Reengineering of the organizational structure and business processes of investment and construction activities. Their place in the general system of corporate regulation - S. B. Sborshikov; N. V. Lazareva (Vestnik MGSU)
Introduction. The formation of an effective organizational structure of construction production management at the corporate level implies adaptation to new conditions. However, in this process, there is a problem of a gap (differentiation) of the plan and action, which requires corrective actions, including with regard to the organizational structure and management processes (business processes) of investment and construction activities. In the future, such impacts will determine the nature of reengineering activities in this area. Business process reengineering and organizational structure reengineering are considered. There is a certain dependence between these types of qualitative organizational transformations, which is primarily due to the transience of the modern life cycle of engineering solutions. Thus, it is possible to identify the purpose of the research — it is a scientific justification for the improvement of the corporate regulation system through reengineering of the organizational structure and business processes of investment and construction activities. On this basis, it is possible to formulate the objectives of the research: to establish the regularity of the gap (differentiation) of the plan and action in the system of corporate governance, to identify the dependence of business processes and organizational structure of investment and construction activities in the context of reengineering of business processes and organizational structure in construction. The object of the research is the system of corporate regulation of investment and construction activities, and the subject is the organizational structure and business processes in construction. From the point of view of practical value, these types of reengineering allow an economic entity to improve the quality and efficiency of construction products by focusing production activities on the consumer and a process approach in management. On this basis it will help to gain competitive advantages, among other things through the wider use of technical means, employees meeting higher requirements of scientific and technical progress and capable of solving complex problems of investment and construction activities, arising at the present stage, in the shortest possible time.Materials and methods. The theoretical basis of the research was a system approach, logistics of regulatory impacts, structural and functional analysis, methods of investment design, strategic and operational management. The information base of the research was the scientific search carried out by the authors earlier, which was reflected in published papers on this subject. Additional sources were scientific works of domestic and foreign scientists, as well as practical materials.Results. The solution of the gap (differentiation) problem in investment and construction activities is shown, which made it possible to propose a scheme of regulation of a construction company, to establish dependencies of business processes and organizational structure of investment and construction activities, as well as dependencies of business process reengineering and organizational structure reengineering in construction.Conclusions. The gap (differentiation) between the plan and the action of a construction organization is caused by fluctuations in the external environment. The main tool for effective adaptation to external fluctuations and corporate regulation is a qualitative transformation of business processes and organizational structure, i.e. their reengineering.